Electrochemical Characterization of Novel Organoborohydride Compounds. (28th July 2016) - Cardoso, David; Sequeira, Cesar A.C.; Bateman, Chris; Barker, Josh; Abbey, Eric; Santos, Diogo M.F.
Abstract : Sodium borohydride (NaBH4 ) has wide application as a reducing agent in organic and inorganic synthesis. In this work, sodium benzylborohydride (C7 H7 BH3 Na) and sodium phenylborohydride (C6 H5 BH3 Na) are synthesized and a direct relationship between the organic substituents and the reducing power of the borohydride center is investigated. Platinum and gold disk macroelectrodes and microelectrodes are used to study the electrooxidation of these organoborohydride compounds. Chronoamperometry and cyclic voltammetry measurements are carried out in dimethyl sulfoxide (DMSO) solution using 0.001 M of each compound at temperatures ranging from 25 to 65 ºC. The results are directly compared to those obtained with NaBH4 solutions in the same experimental conditions. The main electrochemical parameters are evaluated, including number of exchanged electrons, charge transfer coefficients, reaction orders and diffusion coefficients. Moreover, the activation energy for the borohydride oxidation reaction is calculated assuming Arrhenius behavior for the selected range of temperatures.